Mitigating effect of alpha lipoic acid against hematological and renal impairments induced by Flunixin meglumine in male albino rats - El-Maddawy, Zeynab K.; El-Sawy, Abd El-Salam F.; Awad, Amal A. (Journal of Advanced Veterinary Research, 2024)
This study investigated the hematological parameters and renal function effects of Flunixin Meglumine (FM) and assessed the potential protective role of Alpha lipoic acid (ALA) in male rats. Hematological studies, kidney function tests, oxidative stress and antioxidant capacities, kidney weights and index weights, and histopathological studies were evaluated on the 4th and 8th weeks of the experiment. The experiment involved administering FM for 14 successive days and ALA for 56 successive days. Seventy-two (72) male rats were randomly divided into six groups (n=12 animals each): Group 1 (control) received saline and distilled water, Group 2 (ALA) received ALA at a dose level 100mg/kg bwt orally, Group 3 (FM-2.5) received Flunixin meglumine at a dose level (2.5mg/kg bwt) subcutaneously, Group 4 (FM-5) received FM subcutaneously, Group 5 (FM-2.5 and ALA) received FM and ALA, and Group 6 (FM-5 and ALA) received FM and ALA. Flunixin meglumine increased WBCs, serum urea and creatinine levels, MDA, some histopathological changes in kidney tissue, and decreased TAC. These alterations were mitigated by addition of alpha lipoic acid. Non-significant changes in Hb%, P.C.V.%, RBCs and kidney index weight among all treated and control groups. In conclusion, the administration of FM induced hematological and renal impairments in male rats. However, co-administration of ALA effectively mitigated these impairments, suggesting its potential protective role against FM-induced hematological and renal disturbances.